Optimalisasi Pengetahuan Kesehatan Reproduksi Bagi Ibu-Ibu Anggota PW Wyk 4 GKI Getsemani Kotaraja, Jayapura - Eliezer Eliezer; Henderina J. Keiluhu (Bakti Hayati: Jurnal Pengabdian Indonesia, 2022)
Healthy body and health are different things but inseparable. Everyone wants a healthy body and always spare deadly diseases, such as cancer. Knowledge about the most common cancers affecting women and how to prevent them is very important for women everywhere. This paper describes an activity report about exposure to community service activities regarding women's reproductive health, especially socialization about breast cancer and cervical cancer and the ways to prevent them. The target of this activity includes 14 women members of the Women's Fellowship (PW) Wyk 4 Indonesian Christian Church (GKI) Getsemani Kotaraja. The presentation activity took place on August 25, 2021. The results of the implementation of this community service activity showed that the participants could understand the importance of knowledge about reproductive health and could practice the recommendations obtained such as the Breast Self-Exam (BSE-SADARI) Movement, as well as being more sensitive to changes in personal health.Keyword: breast cancer; cervix cancer; SADARI; PW GKI Getsemani.Â